Retrospective study assessing impact of changes in 'management of normal labour' guidelines. (7th June 2011) - Shawkat, E; Myers, J; Mcleod, G; Vause, S
Abstract : Background: Our hospital guidelines were updated following the publication of the National Institute for Health and Clinical Excellence guidelines on intrapartum care. The most significant differences were the change from 3 hourly vaginal examinations to 4 hourly and the diagnosis of onset of labour at 4 cm cervical dilatation rather than 3 cm. Normal progress was defined as 2 cm dilatation in 4 h instead of 1 cm per hour. The aim was to reduce the number of vaginal examinations without reducing the number of normal deliveries or increasing the length of labour, the use of syntocinon, epidural analgesia or the incidence of post-partum haemorrhage (PPH). Aim: To determine whether the new guideline, implemented in November 2008, achieved the expected outcomes. Method: A retrospective case note review was performed. A random sample of women, who delivered in June 2008, was compared with a sample from June 2009. The samples were matched for parity. Women delivering preterm and those planned for elective caesarean section were excluded. Results: 76 women were identified from each month. The number of women having 4 or more vaginal examinations in labour decreased significantly (39/76 to 19/76; p=0.001). The reduction in major PPH, length of labour (491 to 450 min), the use of syntocinon (28/76 to 23/76), epidural analgesia (23/76 to 19/76) and the increase in normal vaginal deliveries (47 to 51) was not statistically significant, although there was a trend towards better outcomes. Summary: Changes to our practice have resulted in fewer vaginal examinations, with a trend towards less intervention and better outcomes.